Guidelines for selection of nickel stainless steels for marine environments, natural waters, and brines (Nickel Development Institute reference book series, 1987)
This publication provides guideline type information that will allow the engineer to take the next step and make a reasonable preliminary estimate of the manner in which the environment is likely to affect the performance of the materials he is considering. The charts and summaries presented provide useful guideposts, but can never serve in place of specific experience, specific data or properly conducted evaluations so necessary to the most successful use of materials. --